Intrinsic capacity and health-promoting lifestyle in older adults: a latent class analysis - Chuyun Xu; Jiaying Yu; Lili Yang; Yu Li; Dongchi Ma (Frontiers in Public Health, 2025)
ObjectivesThis study aims to explore the latent classes and characteristics of older adults’ intrinsic capacity and health-promoting lifestyle, and to investigate the associations between intrinsic capacity and categories of health-promoting lifestyle.MethodsA total of 800 older adults from five communities in Hangzhou, Zhejiang Province, were recruited using a convenience sampling method. Data were collected through the administration of a general information questionnaire, the ICOPE simple screening tool, and the Health Promotion Lifestyle Scale. Latent class analysis is employed to investigate the correlation between intrinsic capacity and health-promoting lifestyle among older adults. Additionally, multinomial logistic regression is utilized to explore the influencing factors associated with different latent classes.ResultsThe intrinsic capacity and health-promoting lifestyle among older adults can be categorized into three latent classes: low psychological-low health type (15%), relatively healthy type (60%), and low cognitive-low participation type (25%). Pearson correlation analysis revealed a significant correlation between intrinsic capacity scores and health-promoting lifestyle scores (r = 0.357, p < 0.001). Age, educational level, number of comorbidities, history of falls within the past 3 months, and sleep duration were identified as significant influencing factors for the latent classes of intrinsic capacity and health-promoting lifestyle among older adults (all p < 0.05).ConclusionIndividuals aged 60 to 79 years, with higher educational levels, ≤2 chronic diseases, no history of falls in the past 3months, and more than 6 h of sleep per day are more likely to be categorized into the relatively healthy type. In contrast, those with ≥3 chronic diseases and less than 6 h of sleep per day are more likely to be classified into the low psychological–low health type.